2015
DOI: 10.1364/ol.40.002037
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal light springs: extended encoding of orbital angular momentum in ultrashort pulses

Abstract: We introduce a new class of spatio-temporally coupled ultrashort laser beams, which are obtained by superimposing Laguerre-Gauss beams whose azimuthal mode index is correlated to their frequency. These beams are characterized by helical structures for their phase and intensity profiles, which both encode the orbital angular momentum carried by the light. They can easily be engineered in the optical range, and are naturally produced at shorter wavelengths when attosecond pulses are generated by intense femtosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 17 publications
2
74
0
Order By: Relevance
“…Recent results showed that EUV harmonic vortices with single-OAM exhibit similar divergence due to OAM conservation262829, thus allowing the synthesization of harmonic vortices into attosecond helical beams, i.e., attosecond pulse trains delayed along the azimuthal coordinate. This particular spatio-temporal light structure, also named “light spring”, results from the addition of harmonic vortices with different topological charges52.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results showed that EUV harmonic vortices with single-OAM exhibit similar divergence due to OAM conservation262829, thus allowing the synthesization of harmonic vortices into attosecond helical beams, i.e., attosecond pulse trains delayed along the azimuthal coordinate. This particular spatio-temporal light structure, also named “light spring”, results from the addition of harmonic vortices with different topological charges52.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, an structured attosecond helical beam –or “structured attosecond light spring”– is obtained, where the linear polarization rotates along the azimuth coordinate. Note that the number of interwinded helices that conform the attosecond helical beam is given by , i.e., the order difference between successive harmonics in the spectrum ( δn ) times the topological charge of the driving beam ()52. While in integer-OAM HHG two interwinded helices were obtained262829, when using fractional-OAM beams a single helix is produced (note that and δn  = 2, as only odd-order harmonics are produced).…”
Section: Resultsmentioning
confidence: 99%
“…In analogy to what was shown in [26], both cases present a helical attosecond pulse train structure, i.e., an attosecond pulse train delayed along the azimuthal coordinate according to the phase variation of the fundamental OAM beam. Note that the helical beam structure is a result of the addition of harmonic vortices with different topological charges [48]. We can observe different helical pulse trains (which for convenience they are plotted in different colors) associated to the path contributions described in the previous section.…”
Section: Helical Attosecond Pulse Trains and Quantum Path Selectionmentioning
confidence: 89%
“…Thus, our results show the possibility of generating helical attosecond pulse trains with different spatio-temporal structures that could be selected depending on the application. These type of helical beams, where not only the phase but also the intensity profile have an helical structure, are beams able to exchange OAM in situations where standard Laguerre-Gauss beams cannot, opening an entire new light-matter interaction regime, [48].…”
Section: Helical Attosecond Pulse Trains and Quantum Path Selectionmentioning
confidence: 99%
“…The structure and properties of helical beams are explored in Ref. [41] in terms of superposition of different OAM modes. Phase-matching control of the temporal and spatial properties of attosecond helical beams is explored in Refs.…”
Section: Xuv Attosecond Helical Pulsesmentioning
confidence: 99%